Emerging biomaterials and strategies for medical applications: a review. (February 2015) - Gangadoo, S.; Chapman, J.
Abstract : The creation of new materials is one of the fundamental driving forces between research and industry and lays the foundation for new products to enhance health and well being for the future. Antibacterial materials are an active area of research but also an economic sector in full expansion that addresses many application domains. It is also a world priority in terms of reducing infection in humans for improved life and well being. Healthcare is one the largest and most rapidly expanding needs of modern society, and smart approaches and materials are required to extend the boundaries required to improve the field. In this paper, we systematically review a series of biomaterials and strategies that have emerged over the last decade. In particular, focus has been driven around the nanorealm. Some of the diverse arenas surrounding the nanodomain and applications include drug screening technologies, biocompatibility, emerging approaches and biomimetics. In a wider front, intelligent materials are where the next phases of research are driven, some of which are discussed herein.